PENGENDALIAN HAMA KEONG EMAS (Pomacea canaliculata Lamarck) PADA TANAMAN PADI SAWAH DENGAN MENGGUNAKAN EKSTRAK BUAH BITUNG (Barringtonia asiatica L.)T EX - Manueke, Jusuf (JURNAL LPPM BIDANG SAINS DAN TEKNOLOGI, 2016)
The study aimed to determine the effect of seed extract Bitung , B. asiatica against golden snail mortality. The experiment was conducted in the village of popontolen, subdistrict Tumpaan, Minahasa Selatan Regency. The duration of less than four months of the study, which lasted from August until November 2013. Research using experimental methods with Complete Randomized Design (CRD) consisting of four treatments and three replications. The treatment used is the concentration of seed extract Bitung 0% (control), 10%, 20% and 30%. Observations death snails performed 6, 12, 24, 30, 42, 54 and 66 hours after application.Symptoms begin with snails death marked the release of mucus from the surface of the body and the body slowly over time regardless of the shells. The observation of 12 hours after the application has been found dead snails in the treatment of Bitung seed extract with all concentration was control is 5.00%, 5% treatment is 18.33%, 10% treatment is 48.33%, 15% treatment is 66.67% and 20 % treatment is 78.33%. The extract concentration 15% was ideal concentration of Bitung Seed to kill the golden Snail because had deadly golden snails above 50%. Therefore the use of Bitung seed extract with a concentration of 15% can already be used to control snails in rice plants.